(untitled) (Bangladesh Journal of Psychiatry, 2020)
Risperidone, a benzisoxazole derivative atypical antipsychotic was more effective than haloperidol (typical antipsychotic) in stimulating prolactin levels. Studies showed that low[1]dose risperidone (0.75-2mg/day, mean (±SD) dose 1.26(±0.42) led to significant increase of serum prolactin levels of different age group after 4-12 weeks of treatment when no patient had other physical condition or adverse effects known to affect prolactin level. Low dose risperidone induced galactorrhea and other physical symptoms in a short period was not a very common one. A 17 years old girl suffering from obsessive compulsive disorder and major depressive disorder developed galactorrhea with breast tenderness and heaviness only 2 weeks after taking low dose risperidone (1 mg). This case report might concern for special attention for prescribing risperidone to young female patients. Bang J Psychiatry 2020; 34(2): 35-37